STUDI METODE-METODE EKSTRAKSI PEWARNA MAKANAN ALAMI ANNATTO DARI BIJI KESUMBA (Bixa orellana) - Johnner Parningotan Sitompul; Martha Situ Situmorang; Tatang Hernas Soerawidjaja (Dept. of Chemical Engineering, Diponegoro University, 2012)
Annatto is natural food colorant extracted from Bixa orellana seeds. The main constituent of annatto is bixin, a carotenoid having carboxylic acid groups at both ends of its molecular chain and one of these is methyl-esterified. The carboxylic acid groups of bixin and norbixin cause the molecule to dissolve in aqueous bases. The methyl ester structure causes the molecule dissolving in oil and other organic solvents. The double bond conjugated chain causes bixin dissolved in most organic solvents. These characteristics are mainly bases for extraction solvent selection. The objectives of this research are to evaluate the performance of ethyl acetate and acetone as solvents for annatto extraction with different method of extraction and to obtain a procedure for preparing general purpose annatto extract having the highest possible of bixin yield. Two methods of extraction are carried out using Soxhlet method (at solvent boiling temperature) and ultrasonic bath extraction at room temperature. The selected solvents are ethyl acetate and acetone that have medium polarity index and low boiling point. The bixin quality is examined by measuring pigment content with spectrophotometer at certain wavelength. Two types of seeds from different places in Indonesia will be the investigated as sources of annatto. Experimental results for extraction with Soxhlet method shows that yield of bixin (upon seed) from ultrasonic bath extraction is higher that is 0.584% (w), compared to Soxhlet extraction 0.443% (w). For ultrasonic bath extraction, yield of bixin (upon seed) with ethyl acetate as solvent is 0.602%, much higher compared to that from acetone 0.565%. Extraction with Soxhlet method gives different results. Yield of bixin (upon seed) with acetone as solvent is higher which is 0.460%, compared to ethyl acetate which is 0.427%. Seeds from Bandung (West Java) and Duri (Riau) do not give significant difference of bixin yield from two methods of extraction. Annatto merupakan pewarna alami makanan yang didapatkan melalui ekstraksi dari biji pohon kasumba (Bixa orellana) dengan komponen pewarna utamanya adalah bixin. Keberadaan ikatan rangkap terkonjugasi menyebabkan bixin dan norbixin larut dalam sebagian besar pelarut organik. Ciri struktur kimia dari bixin ini yang menjadi dasar dalam pemilihan pelarut untuk ekstraksi pewarna annatto. Tujuan makalah ini adalah studi metode-metode ekstraksi terhadap perolehan bixin, metode Soxhlet pada temperatur didih pelarut dan metoda ultrasonic bath pada temperatur kamar, dengan dua tempat sumber biji kasumba, Bandung dan Duri. Pelarut yang digunakan adalah etil asetat dan aseton. Pengujian dilakukan dengan mengukur kadar pigmen yang dihasilkan menggunakan spektrofotometri pada panjang gelombang tertentu. Dari penelitian ini, didapatkan data yield (perolehan bixin) dari berbagai variasi percobaan. Perolehan bixin (terhadap biji) yang didapat dari ekstraksi ultrasonic bath lebih tinggi yaitu rata-rata sebesar 0,584%, dibanding dengan metode soxhlet yang rata-rata sebesar 0,443%. Ekstraksi menggunakan metode ekstraksi ultrasonic bath, dan menggunakan pelarut etil asetat lebih tinggi yaitu rata-rata 0,602% daripada menggunakan aseton yang rata-rata 0,565%. Sedangkan dengan metode soxhlet menunjukkan perolehan bixin berbeda, dengan pelarut aseton 0,460%, sedangkan untuk pelarut etil asetat adalah 0,427%. Biji yang berasal dari 2 tempat berbeda, ketika diekstraksi dengan dua metode tersebut tidak memberikan perbedaaan hasil bixin yang signifikan